Shell shock, memory, and the novel in the wake of World War I - Dodman, Trevor (Cambridge University Press, 2015)
"Shell Shock, Memory, and the Novel in the Wake of World War I explores the narrative traces, subaltern faces, and commemorative spaces of shell shock in wartime and postwar novels by Mulk Raj Anand, Ford Madox Ford, Mary A. Ward, George Washington Lee, Ernest Hemingway, F. Scott Fitzgerald, and Christopher Isherwood. This book argues that World War I novels serve as an untapped source of information about shell shock, and renews our present understanding of the condition by exploring the nexus of shell shock and practices of commemoration. Shell shock novelists testify to the tenaciousness and complexity of the disorder, write survivors into visibility, and articulate the immediacy of wounds that remain to be seen. This book helps readers understand more fully the extent to which shell shock continues to shape and trouble modern memories of the First World War"--